PENGARUH MODEL PEMBELAJARAN INQUIRI TERHADAP RETENSI SISWA DENGAN KEMAMPUAN AKADEMIK RENDAH - Rahmat, Irwandi (Jurnal Biogenerasi, 2025)
This study aims to analyze the effect of Inquiry-based learning model on retention of low-ability students, as well as explore the interaction between learning model and academic ability. Using an experimental design with 2-Way ANOVA technique, this study involved 60 students who were divided into four groups based on academic ability and learning model. The analysis showed that the Inquiry model had a significant effect on the retention of students with low academic ability (p = 0.001), while academic ability itself had no significant effect (p = 0.164). The interaction between learning model and academic ability also showed no significant effect (p = 0.742). LSD test results revealed that the Inquiry - Low group had a higher retention rate compared to the Conventional - Low group. This finding supports the theory of constructivism and provides practical implications for educators to implement more active and participatory learning models for students with low academic ability. Although this study has limitations related to sample size and measurement duration, the results open up opportunities for further research that considers other factors that may affect student retention, such as motivation and social support. Overall, this study contributes to the development of more inclusive and effective learning theories and educational practices.